Particle image velocimetry - Adrian, Ronald J.; Westerweel, Jerry (Cambridge ; New York : Cambridge University Press, 2011)
"Particle image velocimetry, or PIV, refers to a class of methods used in experimental fluid mechanics to determine instantaneous fields of the vector velocity by measuring the displacements of numerous fine particles that accurately follow the motion of the fluid. Although the concept of measuring particle displacements is simple in essence, the factors that need to be addressed to design and implement PIV systems that achieve reliable, accurate, and fast measurements and to interpret the results are surprisingly numerous. The aim of this book is to analyze and explain them comprehensively"--
"Particle image velocimetry, or PIV, refers to a class of methods used in experimental fluid mechanics to determine instantaneous fields of the vector velocity by measuring the displacements of numerous fine particles that accurately follow the motion of the fluid"--
Machine generated contents note: 1. Introduction; 2. Particles; 3. Imaging; 4. Pixelization; 5. PIV systems; 6. Digital image processing; 7. Low image density; 8. High image density; 9. Post processing; 10. Practical guidelines.
Includes bibliographical references (page 529-546) and index.
Keywords: Particle image velocimetry; TECHNOLOGY & ENGINEERING / Mechanical